Variation in the angiosperm ionome - Neugebauer, Konrad; Broadley, Martin R.; El-Serehy, Hamed A.; George, Timothy S.; McNicol, James W.; de Moraes, Milton Ferreira; White, Philip J. (Wiley, 2018)
The ionome is defined as the elemental composition of a subcellular structure, cell, tissue, organ or organism. The subset of the ionome comprising mineral nutrients is termed the functional ionome. A ‘standard functional ionome’ of leaves of an ‘average’ angiosperm, defined as the nutrient composition of leaves when growth is not limited by mineral nutrients, is presented and can be used to compare the effects of environment and genetics on plant nutrition. The leaf ionome of a plant is influenced by interactions between its environment and genetics. Examples of the effects of the environment on the leaf ionome are presented and the consequences of nutrient deficiencies on the leaf ionome are described. The physiological reasons for (1) allometric relationships between leaf nitrogen and phosphorus concentrations and (2) linear relationships between leaf calcium and magnesium concentrations are explained. It is noted that strong phylogenetic effects on the mineral composition of leaves of angiosperm species are observed even when sampled from diverse environments. The evolutionary origins of traits including (1) the small calcium concentrations of Poales leaves, (2) the large magnesium concentrations of Caryophyllales leaves, and (3) the large sulfur concentrations of Brassicales leaves are traced using phylogenetic relationships among angiosperm orders, families and genera. The rare evolution of hyperaccumulation of toxic elements in leaves of angiosperms is also described. Consequences of variation in the leaf ionome for ecology, mineral cycling in the environment, strategies for phytoremediation of contaminated land, sustainable agriculture, and the nutrition of livestock and humans are discussed.